Validity and reproducibility of match-derived ratios of selected external and internal load parameters in soccer players: A simple way to monitor physical fitness? - Schimpchen, J.; Correira, P. F.; Meyer, T. (Biology of Sport, 2023)
The study aim was to assess whether match-derived external-to-internal load ratios are a valid and reliable tool to measure physical fitness. Sixteen elite youth soccer players (17±1 years) performed two maximal fitness tests. Subsequently, players participated in three intra squad soccer matches in three consecutive weeks. Three GPS-based parameters of external load (total distance, PlayerLoad, high-intensity distance) were divided by three heart rate based parameters of internal load (iTRIMP, Banister TRIMP, average percentage heart rate reserve) for the ratio calculations. Validity was established by comparing the ratios with results of the fitness tests, while between-athlete and within-athlete reliability were quantified. Most integrated load ratios were moderately-to-largely correlated with the various fitness parameters. Overall, a ratio consisting of PlayerLoad and average percentage heart rate reserve demonstrated the mostconsistentcorrelations with maximum treadmill speed (r = 0.69, P = 0.003) and the speeds associated with 4 mmol/L of blood lactate (r = 0.56, P = 0.024) and 80% of heart rate reserve (r = 0.54, P = 0.031). Most of the ratios displayed acceptable levels of reproducibility (intraclass correlation coefficient > 0.8 and coefficient of variation < 10%), with the minimal detectable change of all ratios ranging between 7.1 and 37.8%. Given their associations with physical fitness and non-invasive nature, certain external-to-internal load ratios may be used to monitor physical fitness in soccer players. However, the ratios may not be sensitive enough to detect small yet practically relevant alterations in player fitness.